Improvement of Motor Nerve Conduction Velocity in Diabetic Rats Requires Normalization of the Polyol Pathway Metabolites Flux - Takafumi Matsumoto; Yoshiyuki Ono; Masuo Kurono; Akemi Kuromiya; Keiji Nakamura; Vera Bril (Elsevier, 2009)
Using ranirestat, an aldose reductase (AR) inhibitor, we investigated the relationship between sorbitol and fructose levels in the sciatic nerve and motor nerve conduction velocity (MNCV) in streptozotocin (STZ)-treated diabetic rats. Ranirestat inhibited rat and recombinant human AR with similar IC50 values and equipotently prevented sorbitol accumulation in rat erythrocytes and sciatic nerves in vitro. One week after STZ administration, sorbitol levels in rat erythrocytes and sciatic nerves significantly increased while MNCV decreased. Oral administration of ranirestat (0.03 - 1.0 mg/kg per day) for 3 weeks dose-dependently decreased the elevated sorbitol and fructose levels in the rat sciatic nerves without affecting blood glucose level. Particularly, at doses of 0.1 mg/kg per day or higher, ranirestat normalized both sorbitol and fructose levels in the sciatic nerves of STZ-treated rats. Ranirestat (0.1 - 1.0 mg/kg per day) also improved the STZ-induced decrease in MNCV in a dose-dependent manner. This improvement correlated with the decrease of sorbitol and fructose levels in the rat sciatic nerves. These findings indicate that ranirestat improves MNCV via normalization of sorbitol and fructose accumulation in the sciatic nerve. Keywords:: ranirestat, aldose reductase inhibitor, sorbitol, fructose, motor nerve conduction velocity (MNCV)